Development of a decentralized monitoring system of domestic water consumption - Kuski, L. (2019)
Inefficient use of water represents a major source of direct cost of water production, but especially of excessive energy use to purify it. Greater efficiency could be achieved if management were supported by objective data in addition to the rules of good practice that have been disseminated. This work aims to contribute directly to the reduction of water consumption and indirectly to the huge amount of energy used to pump water from its reserves and then to treat and make it drinkable through the use of a decentralized consumption monitoring system.